2011
DOI: 10.1126/science.1200188
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction of RNA Polymerase II and Mediator Required for Transcription in Vivo

Abstract: Gene transcription is highly regulated. Altered transcription can lead to cancer or developmental diseases. Mediator, a multisubunit complex conserved among eukaryotes, is generally required for RNA polymerase II (Pol II) transcription. An interaction between the two complexes is known, but its molecular nature and physiological role are unclear. We identify a direct physical interaction between the Rpb3 Pol II subunit of Saccharomyces cerevisiae and the essential Mediator subunit, Med17. Furthermore, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
131
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 26 publications
6
131
0
Order By: Relevance
“…Factors may bind in the pore, as observed for TFIIS 14 and Gfh1 (ref. 25), or near the RNA exit channel, as observed for Rrn3 (refs 29, 34), the Pol II initiation factor TFIIB that stimulates RNA chain initiation allosterically 47 , and the Pol II coactivator Mediator 48 . The bacterial regulator catabolite activator protein 49 and the growth regulator ppGpp also bind at the RNA exit channel, and the latter was suggested to influence polymerase activity by modulating the coreshelf interface 50 .…”
Section: Discussionmentioning
confidence: 72%
“…Factors may bind in the pore, as observed for TFIIS 14 and Gfh1 (ref. 25), or near the RNA exit channel, as observed for Rrn3 (refs 29, 34), the Pol II initiation factor TFIIB that stimulates RNA chain initiation allosterically 47 , and the Pol II coactivator Mediator 48 . The bacterial regulator catabolite activator protein 49 and the growth regulator ppGpp also bind at the RNA exit channel, and the latter was suggested to influence polymerase activity by modulating the coreshelf interface 50 .…”
Section: Discussionmentioning
confidence: 72%
“…These observations suggested that TFIIS associates at the 59 end of genes and accompanies Pol II and Pol III but cannot be loaded on traveling enzymes. It should be noted that one of the med17 mutants used in this study (med17-257) that showed a UV-sensitive phenotype was lethal in combination with the rpb3-2 Pol II mutation (Soutourina et al 2011) and was affected in Pol II-Mediator interaction (data not shown). However, other med17 mutations with UVsensitive phenotypes did not lead to rpb3-2 colethality phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…yeast and humans (Johnson et al 2002;Lariviere et al 2006;Cai et al 2010;Takahashi et al 2011). Recently, we identified a direct interaction between the Med17 Mediator subunit and the Rpb3 Pol II subunit required for global Pol II transcription in vivo (Soutourina et al 2011). Previously, we showed that a direct contact between the Med11 subunit of Mediator and the Rad3 subunit of TFIIH is essential for the recruitment of the GTF to the PIC independently of Pol II (Esnault et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subunits comprising the evolutionarily highly conserved core Mediator are in bold, subunits required for yeast viability are underlined (adapted from [14] study supported the direct interaction and demonstrated its requirement for Pol II transcription [40 ]. Although human Mediator and Pol II can be co-immunoprecipitated, the human Mediator-Pol II complex cannot be purified in large quantities directly from cells and thus has to be assembled in vitro (personal communication C Bernecky, [41 ]).…”
Section: Interactions With the General Pol II Machinerymentioning
confidence: 99%